An experimental study on the behavior of segmental piles subjected to large lateral displacement - Keklik, Ahmet. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
Segmental model piles are composed of alternating concrete blocks and rubber sheets connected by a steel wire which can be tensioned to a desired force. One of the claims for these types of piles is the ability to undergo large horizontal displacements. To test this claim model segmental piles with 750N and 2250N tension force were placed into loose and medium dense sand and 50 mm lateral displacement was applied. The pile head load was measured. Magnetometers placed on each concrete block were calibrated to obtain the inclination of each block and an algorithm was developed to calculate lateral displacements along the pile from inclinations. The standard deviation of inclination values was 0.36, 0.60, and 1.71 degrees for 7.5, 15, and 22.5 degrees of inclination values respectively. Although the piles were classified as short piles, The 750N segmental pile demonstrated a flexible pile behavior for loose and dense sand conditions. The 2250 N segmental pile behaved similarly to that of a rigid pile for the loose sand condition. For the medium dense sand, the behavior changed to that of flexible pile. The horizontal capacity of 750 N pile reached to 500N for medium dense sand at 50 mm displacement coming close to 700N load measured for 2250N segmental pile under similar conditions. Both segmental piles did not show any structural failure signs under large lateral displacement.
Keywords: Piling (Civil engineering)